2011
DOI: 10.1371/journal.ppat.1001343
|View full text |Cite
|
Sign up to set email alerts
|

Low Diversity Cryptococcus neoformans Variety grubii Multilocus Sequence Types from Thailand Are Consistent with an Ancestral African Origin

Abstract: The global burden of HIV-associated cryptococcal meningitis is estimated at nearly one million cases per year, causing up to a third of all AIDS-related deaths. Molecular epidemiology constitutes the main methodology for understanding the factors underpinning the emergence of this understudied, yet increasingly important, group of pathogenic fungi. Cryptococcus species are notable in the degree that virulence differs amongst lineages, and highly-virulent emerging lineages are changing patterns of human disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 88 publications
11
100
1
Order By: Relevance
“…A recent epidemiological study has shown that clinical and environmental isolates in Thailand predominantly consist of 3 STs, ST44, ST45, and ST46, accounting for up to 90z of the total isolates investigated (14), indicating low genetic diversity. In Japan, Mihara et al (15) has reported that 31 of the 35 isolates in Nagasaki, Japan exhibited ST5.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent epidemiological study has shown that clinical and environmental isolates in Thailand predominantly consist of 3 STs, ST44, ST45, and ST46, accounting for up to 90z of the total isolates investigated (14), indicating low genetic diversity. In Japan, Mihara et al (15) has reported that 31 of the 35 isolates in Nagasaki, Japan exhibited ST5.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy of ST might be due to the MLST database; http://cneoformans.mlst.net and http://mlst.mycology lab.org are used for this study and the study of Mihara et al, respectively. To compare STs in this study with the large-scale investigation by Simwami et al (14), we adopted the former database. A Chinese epidemiological study has shown that the majority of C. neoformans isolates exhibited the same ST, in which the nucleotide sequences of 5 loci examined (GPD1, IGS1, LAC1, PLB1, and SOD1) are identical to those of ST46 (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations